2016
DOI: 10.1161/atvbaha.116.307743
|View full text |Cite
|
Sign up to set email alerts
|

AMP-Activated Protein Kinase α1 in Macrophages Promotes Collateral Remodeling and Arteriogenesis in Mice In Vivo

Abstract: A rteriogenesis is a process of developing collateral circulation through the remodeling and growth of pre-existing collateral arteries after elevated shear stress induced by occlusion.1-3 Arteriogenesis takes place both during embryogenesis and in adult tissues. In the latter case, arteriogenesis, which usually occurs at sites of occlusion or physical disruption of pre-existing arterial conduits such as coronary artery occlusion or femoral artery ligation, plays a vital role in recovery from ischemic insults.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 46 publications
(61 reference statements)
0
17
0
Order By: Relevance
“…Although in our study the role of AMPKα2 deletion in neutrophils was more pronounced, it is possible that the AMPKα1 isoform plays a significant role in the regulation of monocyte function as described in an article published during the revision of this article. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Although in our study the role of AMPKα2 deletion in neutrophils was more pronounced, it is possible that the AMPKα1 isoform plays a significant role in the regulation of monocyte function as described in an article published during the revision of this article. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, macrophages not only secrete proangiogenic but also angiostatic factors . In vivo, a recent study showed that animals deficient for 5′AMP‐activated protein kinase (AMPK)α1 in macrophages exhibit a reduced remodeling of collateral arterioles after femoral artery ligation . We previously showed that in the same deficient animals, macrophages hardly acquire the restorative anti‐inflammatory phenotype during skeletal muscle regeneration (see below section Role of AMPK in macrophages during skeletal muscle regeneration) , suggesting that restorative macrophages are required for an efficient angiogenesis during muscle regeneration.…”
Section: Macrophages During Skeletal Muscle Regenerationmentioning
confidence: 99%
“…Angiogenesis is induced by hypoxia and involves three cells: tip cells, stalk cells, and phalanx cells [3][4][5], while the main stimulus of arteriogenesis is fluid shear stress (FSS), which is sensed by endothelial cells and consequently attracts leukocytes and promotes the phenotype transformation of vascular smooth muscle cells (VSMCs) [6][7][8][9]. Signal pathways of these two ways both include vascular endothelial growth factor (VEGF) pathway and nitric oxide-(NO-) dependent pathway [10][11][12][13][14] and both of them can be regulated by a highly conserved eukaryotic kinase, 5′adenosine monophosphate-activated protein kinase (AMPK) [15][16][17]; SNF1 and SnRK1 are its orthologues in yeast and several plants [18].…”
Section: Introductionmentioning
confidence: 99%